Sapulun : Pamali Lisan Dalam Membentuk Profil Pelajar Pancasila Serta Kaitannya Dengan Musibah Di Kalimantan - Ahmad Saefulloh; Maryam Mustika; Ali Sunarno; Eddy Lion; Vera Anggraini (Institut Agama Hindu Negeri Tampung Penyang Palangka Raya, 2023)
One of the causes of the disappearance of a culture is the reduction in cultural actors implementing it in society, a sense of shame, prestige and outdated assumptions (Zakarias, 2020). Sampulun, is a culture found in Central Kalimantan as a form of respect for the host who offers dishes by touching the food container. This culture requires survey data on whether the current generation of teenagers, especially middle and high school students, apply the philosophy and actual implementation of Sampulun culture in society and how it relates to the profile of Pancasila students. This research uses qualitative action research methods. Qualitative methods were used to explore and explore the existence and philosophical meaning of Sampulun culture in the people of the Kahayan River Basin in Palangka Raya City. Action research is used to implement character values in Sampulun culture for middle and high school students in Palangka Raya City to strengthen the Pancasila Student Profile. Data collection techniques use observation, surveys and interviews. The data analysis technique uses an interactive model from Miles & Huberman which consists of four components, namely data collection, data reduction, data presentation, and drawing conclusions. The results of the research found that the cover can shape the character profile of Pancasila students through the formation of the character of believing in God Almighty, that disaster cannot be separated from the will of God, the cover also forms a character of respect for nature and humans, through the presence of pamali that develops to form an attitude of respect for cultural differences and wisdom existing local areas, as well as forming characters with global diversity, creative and critical reasoning with attitudes that emerge from students in the form of respect for other people's cultures. These findings show that the cover has the function of forming morals, culture, religion and health through educating students' values Pancasila.